Elective induction of labour at 39 weeks versus expectant management up to 41 weeks in a tertiary care centre - Kabadi, Yogindra M.; Kumar, Sanjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The timing of delivery and effective management of labour at term makes a huge difference in the obstetric and perinatal outcome. There have always been controversies between choosing the elective induction of labour at 39 weeks versus expectant management up to 41/42 weeks which can result in placental ageing, reduced liquor, non-assuring fetal heart tracings, meconium stained amniotic fluid and fetal macrosomia. our objective was to perform a comparative effectiveness analysis of elective induction of labor at 39 weeks gestational age among nulliparous women with uncomplicated singleton pregnancies as compared to expectant management up to 41 weeks. Methods: 120 primigravidae with singleton pregnancies with fetus in cephalic presentation were recruited into the study and divided into 2 groups of 60 each A: Patients were induced electively using dinoprostone gel (maximum 3 doses 8 hours apart) B: They were managed expectantly up to 41 weeks allowing for spontaneous onset of labour, induction or cesarean section was done for obstetric indications between 39 and 41 weeks and pregnancy was terminated by induction for those who continued up to 41 weeks. Their obstetric and perinatal outcome were noted. Results: The cesarean section rates were higher in the expectantly managed group (21%) when compared to the electively induced group (16%). The same was with instrumental delivery rates (15% versus 10%). The perinatal outcome was poorer for the expectantly managed group with 20% NICU admissions and 5% perinatal deaths compared to the electively induced group which had 12% NICU admissions and 3.3% perinatal deaths. The expectantly managed group also resulted in respiratory distress in a larger number of fetuses and resulted in problems due to reduced liquor. Conclusions: Elective induction at 39 weeks gestational age was found to be a better option compared to expectant management up to 41 weeks in terms of obstetric and perinatal outcomes.